2020
DOI: 10.1177/1350650120974132
|View full text |Cite
|
Sign up to set email alerts
|

Effect of friction modifiers compositions on tribological properties of Cu-Sn alloy/Al2O3 brake composite material

Abstract: Brakes are very important component in any vehicle, used to stop the motion of it either by applying mechanical or hydraulic pressure on brake pads. By engaging and disengaging of braking action, the surface of brake components (or) materials is ruined after some time. Therefore, it is important to study and develop a new composition of brake materials which provides optimum coefficient of friction along with increasing wear resistance to the materials. Hence, new combination has been formulated for fabricatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Further, the abrasive wear and formation of oxide layer are possible wear mechanism at higher applied loads while adhesive wear is possible wear mechanisms at lower loads. A similar observation is reported by Sing et al 42 in their research work that is carried out on sintered composite of Cu-Sn alloy/Al 2 O 3 /graphite/talc.…”
Section: Resultssupporting
confidence: 88%
“…Further, the abrasive wear and formation of oxide layer are possible wear mechanism at higher applied loads while adhesive wear is possible wear mechanisms at lower loads. A similar observation is reported by Sing et al 42 in their research work that is carried out on sintered composite of Cu-Sn alloy/Al 2 O 3 /graphite/talc.…”
Section: Resultssupporting
confidence: 88%
“…With the activation and deactivation of braking, the surface of brake components or materials deteriorates after a while. For such reasons, it is important to develop brake material components that provide the optimum friction coefficient with the increased wear resistance occurring in the materials (Singh et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it has been concluded that the adhesive, abrasive, and plow wear are possible to wear mechanisms at the counterface. Singh et al 30 investigated the tribological performance of Cu–Sn alloy/Al 2 O 3 /graphite/talc composite, fabricated by the powder metallurgy technique and observed a similar phenomenon.…”
Section: Resultsmentioning
confidence: 84%